A Villa in Sicily: Figs and a Cadaver (A Cats and Dogs Cozy Mystery-Book 2) - Fiona, Grace (Lukeman Literary, 2020)
"Very entertaining. Highly recommended for the permanent library of any reader who appreciates a well-written mystery with twists and an intelligent plot. You will not be disappointed. Excellent way to spend a cold weekend!" --Books and Movie Reviews (regarding Murder in the Manor) A VILLA IN SICILY: FIGS AND A CADAVER is book #2 in a charming new cozy mystery series by bestselling author Fiona Grace, author of Murder in the Manor, a #1 Bestseller with over 100 five-star reviews (and a free download)! Audrey Smart, 34, has made a major life change, walking away from her life as a vet (and from a string of failed romance) and moving to Sicily to buy a $1 home-and embark on a mandatory renovation she knows nothing about. Audrey is busy working to open the town's new shelter, while also renovating her own problematic home-and dating again. With the help of friends, she begins taking in sick strays. But not everyone in town is grateful for her services, and she soon makes unexpected enemies. When Audrey gets a tip about an injured dog near the coast and goes to find him-she finds the dead body of a powerful local instead. Can Audrey, now a suspect, solve the crime and clear her name? Or will her Sicilian dream fall apart? A laugh-out-loud cozy packed with mystery, intrigue, renovation, animals, food, wine-and of course, love-A VILLA IN SICILY will capture your heart and keep you glued to the very last page. "The book had heart and the entire story worked together seamlessly that didn't sacrifice either intrigue or personality. I loved the characters - so many great characters! I can't wait to read whatever Fiona Grace writes next!" --Amazon reviewer (regarding Murder in the Manor) "Wow, this book takes off & never stops! I couldn't put it down! Highly recommended for those who love a great mystery with twists, turns, romance, and a long lost family member! I am reading the next book right now!" --Amazon reviewer (regarding Murder in the Manor) "This book is rather fast paced. It has the right blend of characters, place, and emotions. It was hard to put down and I hope to read the next book in the series." --Amazon reviewer (regarding Murder in the Manor) Book #3 in the series-VINO AND DEATH-is now also available!
Keywords: Krimi, detektivky